"Versagtende omstandighede" by moord en verkragting in die Suid-Afrikaanse strafreg - Janeke, C. M. (University of the Free State, 1976)
Abstract not available
Dissertation (LL.B. (Law))--University of the Free State, 1976
Keywords: Criminal liability; Murder; Rape; Criminal law